Expression of the receptor tyrosine kinase recepteur d'origine nantais and its association with tumor progression in hypopharyngeal cancer. Issue 8 (6th August 2012) - Yoon, Tae Mi; Kim, Sun‐Ae; Park, Young‐Lan; Lee, Kyung‐Hwa; Sung, Myung‐Whun; Lee, Joon Kyoo; Lim, Sang Chul; Chung, Ik‐Joo; Joo, Young‐Eun
Abstract Background The purpose of this study was to investigate expression of recepteur d'origine nantais (RON) in human hypopharyngeal squamous cell carcinoma (SCC) and to determine whether RON affects tumor cell behavior in hypopharyngeal SCC cell line and if this would serve as a target for molecular therapy in a preclinical model. Methods Reverse transcriptase‐polymerase chain reaction, immunohistochemistry, Western blotting, cell invasion, migration, proliferation, and apoptosis assays were used to assess alteration of RON expression and its impact to cancer progression in human hypopharyngeal SCC. Results Immunoreactivity of RON was observed in hypopharyngeal SCC tissues relative to adjacent normal mucosa in all cases. RON protein expression was significantly increased in metastatic lymph nodes than nonmetastatic lymph nodes by Western blotting. Knockdown of RON resulted in significantly reduced cell invasion, migration, and proliferation in human hypopharyngeal SCC cells. Knockdown of RON enhanced cell apoptosis through activation of caspase 3, caspase 7, and poly ADP‐ribose polymerase (PARP). Conclusion These results indicate that knockdown of RON expression may be associated with the reversal of invasive phenotype in hypopharyngeal SCC. © 2012 Wiley Periodicals, Inc. Head Neck, 2013